Stadt- und Raumentwicklung mithilfe Künstlicher Intelligenz?! - (:unkn) unknown (My University, 2024)
Artificial intelligence has found its way into spatial development and requires a responsible approach from the stakeholders involved. Municipalities are using AI to improve citizen services, participation processes and mobility services, for example. In this article, fields of application and prerequisites for the use of AI are presented before addressing five specific areas of spatial development: the physical infrastructure of servers and data centers, smart city approaches, platform economy, intra-urban inequalities and the urban-rural divide. The opportunities and risks of using AI discussed in the literature are outlined. The spatial planning profession is also facing changes as a result of AI, with new possibilities for analyzing, processing and presenting data, participation formats and the management of planning processes. In the concluding chapters, some recommendations for the welfare-oriented and sustainable use of AI in municipalities are formulated before the contents of the special issue are presented.
Eine Einführung
Keywords: Stadtentwicklung; Raumentwicklung; Künstliche Intelligenz; KI